Molecular Structure and Vibrational Spectra of Iodotrimethylgermane (GeIMe 3 ) by Theory and Experiment - Roldán, María L. (2007)
The geometry of iodotrimethylgermane has been determined by experimental and computational methods. Fourier transform infrared spectra have been recorded over a range of temperatures along with the Raman spectrum to obtain comprehensive vibrational data for the fundamental modes. The stretching, rocking, and deformation bands of the methyl groups have been resolved into their components with the aid of lowtemperature infrared spectroscopy using Fourier self-deconvolution and curve-fitting methods. The optimized geometries and vibrational harmonic frequencies were calculated by density functional theory methods employing Pople-type basis sets, as well as those with descriptions for an effective core potential describing both germanium and iodine atoms. A scaled quantum mechanical analysis was carried out to yield the best set of harmonic force constants and obtain a transferable set of scale factors that can be applied to the (CH3)3- GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. GeX (X ) H, Cl, Br, I) series. 3)3- GeX (X ) H, Cl, Br, I) series.) H, Cl, Br, I) series.